2014
DOI: 10.1007/s40879-014-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Total Thue colourings of graphs

Abstract: We show that the strong total Thue chromatic number π T (G) < 15 2 for a graph G with maximum degree ≥ 3, and establish some other upper bounds for the weak and strong total Thue chromatic numbers depending on the maximum degree or size of the graph. We also give some lower bounds and some better upper bounds for these graph parameters considering special families of graphs. Moreover, considering the list version of the problem we show that the total Thue choice number of a graph is less than 18 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…The notion of Total Thue coloring was introduced by Schreyer andŠkrabuvláková [17]. A coloring of the edges and the vertices of a graph is a weak total Thue coloring if the sequence of consecutive vertex-colors and edge-colors of every path is non repetitive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of Total Thue coloring was introduced by Schreyer andŠkrabuvláková [17]. A coloring of the edges and the vertices of a graph is a weak total Thue coloring if the sequence of consecutive vertex-colors and edge-colors of every path is non repetitive.…”
Section: Introductionmentioning
confidence: 99%
“…These two parameters both have there list-coloring counterpart denoted respectively by π Twch (G) and π Tch (G). Schreyer andŠkrabuvláková [17] showed that π T (G) 5∆ 2 +o(∆ 2 ), π Tch (G) 17.9856∆ 2 and π Tw (G) |E(G)| − |V (G)| + 5. We remark that the second bound also relies on an application of the Lovász Local Lemma.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is also well-studied in the nonrepetitive setting [18,24,25,29,35,46,47,48]. A nonrepetitive vertex L-colouring of G is a nonrepetitive vertex colouring c of G in which c(v) ∈ L(v) for every vertex v ∈ V (G).…”
Section: List Colouringsmentioning
confidence: 99%
“…A total colouring is a colouring in which both edges and vertices of a graph are coloured such that no adjacent edges, and no edge and its endpoints, are assigned the same colour. Such colourings were also studied in the nonrepetitive setting by Schreyer andŠkrabul'áková [48]. They defined two versions of the problem.…”
Section: Total Thue Chromatic Numbermentioning
confidence: 99%
See 1 more Smart Citation